Measuring intellectual capital: a review of recent literature / Delilah S. Juan, Amrizah Kamaluddin and Ellen Chung - S. Juan, Delilah; Kamaluddin, Amrizah; Chung, Ellen (2023)
Intellectual capital is a critical intangible asset that may provide a sustainable competitive advantage to a firm. The Value Added Intellectual Coefficient (VAIC) developed by Pulic (2000) as a measure of intellectual capital (IC) efficiency has been widely adopted in research on its impact on corporate financial performance. This measure of IC efficiency, composed of human capital efficiency, structural capital efficiency and capital employed efficiency, represents the value generated by the firm with its intangible and tangible resources. However, following their evaluation of Pulic’s VAIC model, these researchers have proposed adjustments and extensions to it. Hence, this paper reviews and examines these modifications to the VAIC model to determine the new components added. Recent research papers published between 2017 and 2022 were analysed. These papers were derived from the Scopus and Web of Science databases. The keywords used were “intellectual capital”, “VAIC”, and “financial performance”. Although most IC research still adopts Pulic’s VAIC model, some new research made adjustments to the components in the original model. Other researchers have added components to it such as innovation, relational, and process capital. The findings of this review will enable a better understanding of the conceptualisation and measurement of IC. The new components added by researchers in the model may enhance the value added by the firm’s resources towards competitive advantage. The new components added by researchers in the model may enhance the value added by the firm’s resources towards competitive advantage. This paper contributes to current literature by providing an overview of recent developments in measuring intellectual capital